Pengaruh Literasi Keuangan Dan Gaya Hidup Terhadap Perilaku Pengelolaan Keuangan Pada Siswa SMKN 1 Jetis - Sofia Dewi Anggraini; Nersiwad Nersiwad; Yuliasnita Verlandes (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The development of financial management was pioneered by the behavior of a person in the decision-making process. Financial management must lead to responsible financial behavior so that all finances for both individuals and families can be managed properly. Early financial planning will help a person to realize his life goals. A student is an age at the stage of self-development to establish attitudes and lifestyle behaviors and be able to carry out good financial planning by understanding financial literacy correctly. This research was conducted by distributing questionnaires via Google form to students at SMKN 1 Jetis who met the research criteria, namely ages 16-18 years. The research sample was 1256 students using a purposive sampling technique, so that 93 respondents were needed. The data analysis technique uses multiple linear regression data analysis with the help of SPSS 25. The results show that the financial literacy variable has a positive and significant influence on financial management behavior, lifestyle has a positive and significant influence on financial management behavior, and financial literacy and lifestyle variables simultaneously influence the behavior of financial management.